CTS Research E-News (September 2007) - Center for Transportation Studies (Center for Transportation Studies, University of Minnesota, 2007)
Articles include: Policy and Planning, Oberstar Forum to focus on nation’s transportation infrastructure, Intelligent Transportation Systems, Final rural intersection safety reports: technology to prevent crashes, Advanced Transportation Technologies Seminar series, Civil engineering researcher gets SMART, Safety, Technology to help teens drive safely, Transportation Infrastructure, New design requirements for Minnesota low-volume concrete pavements, Upcoming Events, James M. Oberstar conference on Transportation Policy and Technology, ITS Minnesota Fall Forum, CTS 20th Anniversary Reception, Minnesota Public Transit Conference, CTS Freight and Logistics Symposium
Keywords: Transportation